Sistem Peramalan Harga Emas Antam Menggunakan Double Exponential Smoothing - Andriyanto, Teguh (Universitas Nusantara PGRI Kediri, 2017)
Gold is one of the long-term investment items. The price of gold at any time may change. For someone who invests in gold, of course, requires information changes in gold prices so he can determine when to buy or sell gold. Without accurate information it will be difficult to determine the value or price of gold a few months or years ahead. In this study built prototype information system forecasting gold price of Antam. Monthly historical data of Antam gold price is downloaded from the official website of Antam in excel format. Further excel files are uploaded and processed to determine the forecast price of gold some period to the fore. Forecasting information system is built using PHP programming language and MySql database. The results of forecasting error testing show the accuracy of forecasting of 87.34%. Dara 78 pricing and forecasting data obtained 60 data value tracking signal is beyond the limits of control.